INSTITUTIONAL BETRAYAL IN HEALTHCARE: A SYSTEMATIC LITERATURE REVIEW OF HOSPITAL RESPONSES TO PATIENT REPORTS OF PHYSICIAN-PERPETRATED SEXUAL HARASSMENT - Pajung, Christian Bertom (Universitas Negeri Manado, 2025)
It is wrong in opposition to the law for doctors to sexually harass their patients. The focus of research has transitioned from individual transgressions to institutional failures to respond, termed institutional betrayal. This failure might cause more distress and make patients less trusting. The purpose of this comprehensive analysis of the literature is to find and examine instances of institutional betrayal as well as trends in hospital reactions to patient complaints of sexual harassment by doctors. This meta-analysis was performed according to the PRISMA 2020 statement. Fist search in Scopus and PubMed were originated 100 articles that narrowed to 8 original research). Quality of data was extracted and assessed for risk of bias using MMAT. Synthesis was carried out narratively and qualitatively. This review was conducted according to PRISMA 2020. A preliminary screen of relevant articles in Scopus and PubMed, extracted potential papers published a total of 100 papers and were subsequently narrowed down to eight eligible original research paper. MMAT was employed to extract and evaluate the quality of related data. Synthesis was an interpretative/qualitative narrative. Eight of the studies reviewed showed low to very low risk of bias. The focus of scholarly inquiry moved from patient reactions (1981) to an examination of institutional responses (2017-2022). Three clusters of hospital responses were observed: Negative/Passive, Formal/Inconsistent, and Proactive/Comprehensive. An institutional betrayal was driven by Negative/Passive and Formal/Inconsistent responses through structural. One important factor influencing the post-report outcome for patients is the institutional response. To reduce institutional betrayal and rebuild patient trust, hospitals should take a proactive, all-encompassing approach (institutional courage).